PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA PADA PT HM SAMPOERNA TBK PEKANBARU - Fery Hendra; Machasin '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the influence of job satisfaction and organizational commitment to performance through discipline employees working at PT. HM Sampoerna Tbk Pekanbaru. This study using 98 samples. The analytical method used is descriptive analysis method is a way to test variables, regression test, and the last test path analysis or path analysis.From the results of testing that has been done, the effect obtained directly between job satisfaction variables affect the performance by 0.184, which means 18.4% of the variable performance is influenced by variables of job satisfaction, organizational commitment to employee performance effect of 0.192 which means that 19.2% of employee performance influenced by organizational commitment. For the variable of job satisfaction on work discipline effect of 0.404, which means 40.4% of employee performance is affected by organizational commitment. For the indirect effect is the effect of job satisfaction on employee performance through the discipline of work to get the 0.192. The influence of organizational commitment to performance through the discipline of work to get the results for 0.201, which means an indirect influence between organizational commitment to performance through disciplined work affects 20.1%.Keywords: Job Satisfaction, Organizational Commitment, Discipline of Work and Employee Performance